Relationship between water mass characters to Sound velocity profiler (SVP) in the Sulawesi Sea - Agustinus Agustinus; Widodo Setiyo Pranowo; Henry Munandar Manik; Amri Rahmatullah; Tri Aji (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
The Sulawesi Sea is the western entry point of the Indonesian throughflow, which brings water masses from the Pacific Ocean. This study aims to describe the relationship between water mass characteristics and Sound Velocity Profiler (SVP) in the Sulawesi Sea based on Marine Copernicus data from 2022 with a depth of up to 500 meters. Temperature and Salinity data were used to obtain water mass types from the Tpot-S diagram based on Emmery's classification and Sound Velocity Profiler (SVP) based on the Medwin empirical equation. The temperature, salinity, and SVP data were visualized using ODV 5.6.2 software. The data processing results have identified several water mass characteristics that are believed to be influenced by the Eastern North Pacific Central Water (ENPCW) water mass type found at depths ranging from 130 to 318 meters, Western North Pacific Central Water (WNPCW) water mass found at depths ranging from 130 to 500 meters, Eastern South Pacific Central Water (ESPCW) water mass found at depths ranging from 92 to 453 meters, and Western South Pacific Central Water (WSPCW) water mass found at depths ranging from 130 to 500 meters. The ENPCW water mass type on average has a smaller difference in SVP values compared to the WNPCW water mass type. Meanwhile, the ESPCW water mass type on average has a greater difference in SVP values compared to the WSPCW water mass type. The results indicate a positive relationship between temperature and SVP, meaning that the higher the temperature, the higher the SVP. However, there is a negative relationship between salinity and SVP, meaning that the higher the salinity, the lower the SVP.Keywords:Water MassTemperatureSalinitySound VelocitySulawesi Sea